Improving Health Care Competence of Future Teachers Based on Digital Educational Technologies (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, there are thoughts and opinions about improving the health care competence of future teachers based on digital technologies. In today's world, teachers play a crucial role in shaping the minds and lives of young learners. While their primary focus is on academic development, it is equally important for teachers to possess a certain level of healthcare competence. By equipping future teachers with the necessary knowledge and skills in healthcare, we can ensure the well-being and safety of students, creating a conducive learning environment.